Preventive behaviour at work – A concept analysis. (4th July 2017) - Lecours, Alexandra; Therriault, Pierre-Yves
Abstract: Background: Preventive behaviour is a significant intervention target in order to promote health at work, but has never been discussed in an occupational perspective. Aim: To clarify the concept of preventive behaviour at work. Methods: The Walker and Avant (2011) method was used to conduct the study. Results: The attributes of the concept are: (1) compliance with safety rules and procedures, (2) proactivity, participation, engagement and initiatives related to prevention, (3) maintenance of physical environment, (4) concern for social environment and (5) reflexivity and analytical skills of work situations. The analysis also identified the antecedents and the consequences of the concept that are all related to either the person, the environment or the occupation. Conclusion: Preventive behaviour occurs when a worker shows an active involvement to comply with safety rules and procedures of his trade, takes initiatives to improve prevention, preserves his physical environment, communicates with his peers and analyses work situations before committing to it. Significance: Occupational therapists have a central role in primary prevention of work injuries and have the expertise to help develop each of the five attributes of the concept of preventive behaviour.